Impact of Social Media Influences on the Consumption Behavior of Adolescents and Children - Muhamad Hanafiah; Irwansyah Irwansyah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research is a qualitative study and literature study. This study examines how social media influencers influence the behavior of teenagers and their impact on them. The results showed that social identity, source credibility, and quality of information are factors that have an impact on adolescent consumer behavior where these three things are to encourage purchase intentions and behavior of adolescent consumers. The results of the study also show that the impact of the influencer's social media exposure is the increase in materialism from teenagers which also encourages consumptive behavior from teenagers. The results of this study are an illustration of how influencers have on teenagers. For business people and businesses, this research can be used as input in an effort to increase the effectiveness of the use of influencers for the youth market. Meanwhile, for individual teenagers and parents, this research can also be information to limit teenagers in bad behavior such as materialism which leads to waste.